Implant‐supported mandibular removable partial dentures: Functional, clinical and radiographical parameters in relation to implant position. (20th March 2017) - Jensen, Charlotte; Speksnijder, Caroline M.; Raghoebar, Gerry M.; Kerdijk, Wouter; Meijer, Henny J. A.; Cune, Marco S.
Abstract: Background: Patients with a Kennedy class I situation often encounter problems with their removable partial denture (RPD). Purpose: To assess the functional benefits of implant support to RPDs, the clinical performance of the implants and teeth and to determine the most favorable implant position: the premolar (PM) or molar (M) region. Materials and methods: Thirty subjects received 2 PM and 2 M implants. A new RPD was made. Implant support was provided 3 months later. In a cross‐over model, randomly, 2 implants (PM or M) supported the RPD during 3 months. Masticatory performance was assessed using the mixing ability index (MAI). Clinical and radiographic parameters were assessed. Non‐parametric statistical analysis for related samples and post hoc comparisons were performed. Results: Masticatory performance differed significantly between the stages of treatment ( P < .001). MAI‐scores improved with implant support although the implant position had no significant effect. No complications to the implants or RPD were observed and clinical and radiographical parameters for both implants and teeth were favorable. Higher scores for bleeding on probing were seen for molar implants. Conclusions: Implant support to a Kennedy class I RPD significantly improves masticatory function, regardless of implant position. No major clinical problems were observed.